The influence of life commitments and emotion regulation on coaching effectiveness - Davis, P.; Davis, L.; Dinning, S. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Sport coaches are often volunteers with numerous life commitments (e.g., jobs, family) outside of the domain of sport. The influence of life commitments and associated stress on athletes` performance has been shown to be significant; however, coaching effectiveness has not been examined in relation to coaches` personal responsibilities. Therefore, the aim of this study was to analyse the influence of life commitments, perceived stress and emotion regulation on coaching effectiveness. Methods: Thirty level three (UKCC) coaches from the United Kingdom completed questionnaires measuring perceived stress, coaching effectiveness and emotion regulation. Additionally, coaches completed a qualitative writing task exploring their perceptions of the influence of life commitments on their coaching effectiveness. Linguistic analyses were conducted on the writing transcripts to investigate participants` expressions of emotions and indicators of cognitive processes (e.g., insight, causation). Results: Coaches reported experiencing a range of life commitments (e.g., education, relationships) and a variety of emotions (e.g., joy, anger, sadness) associated with personal responsibilities outside of the domain of sport. Coaches perceived their life commitments to be both positive (e.g., financially enabling sport participation) and negative (e.g., causing fatigue) influences on their coaching effectiveness. In particular coaches who reported high levels of perceived stress reported that life commitments were more detrimental to their coaching effectiveness. Linguistic analyses revealed that coaches felt that they largely understood the influence of life commitments on their emotions and coaching effectiveness. Coaches` attempts to cope with perceived stress also emerged as a theme in the qualitative analyses. Discussion: Coaches` perceived effectiveness can be influenced by the life commitments they experience outside of sport. The regulation of coaches` emotions and the ability to manage perceived stress can reduce the detrimental effects of personal responsibilities on coaching effectiveness. The implications of life commitments on coaching effectiveness have received limited research attention; interventions aimed at developing effective emotion regulation may help coaches cope with perceived stress, enhance coaching effectiveness and prevent burnout.